Enhanced Phosphorylation-Independent Arrestins and Gene Therapy - Gurevich, Vsevolod V. (Handb Exp Pharmacol, 2014)
A variety of heritable and acquired disorders is associated with excessive signaling by mutant or overstimulated GPCRs. Since any conceivable treatment of diseases caused by gain-of-function mutations requires gene transfer, one possible approach is functional compensation. Several structurally distinct forms of enhanced arrestins that bind phosphorylated and even non-phosphorylated active GPCRs with much higher affinity than parental wild-type proteins have the ability to dampen the signaling by hyperactive GPCR, pushing the balance closer to normal. In vivo this approach was so far tested only in rod photoreceptors deficient in rhodopsin phosphorylation, where enhanced arrestin improved the morphology and light sensitivity of rods, prolonged their survival, and accelerated photoresponse recovery. Considering that rods harbor the fastest, as well as the most demanding and sensitive GPCR-driven signaling cascade, even partial success of functional compensation of defect in rhodopsin phosphorylation by enhanced arrestin demonstrates the feasibility of this strategy and its therapeutic potential.